Do children use different forms of verbal rehearsal in serial picture recall tasks? A multi-method study. Issue 6 (3rd July 2019) - Poloczek, Sebastian; Henry, Lucy A.; Messer, David J.; Büttner, Gerhard
ABSTRACT: Use of verbal rehearsal is a key issue in memory development. However, we still lack detailed and triangulated information about the early development and the circumstances in which different forms of rehearsal are used. To further understand significant factors that affect children's use of various forms of rehearsal, the present study involving 108 primary school children adopted a multi-method approach. It combined a carefully chosen word length effect method with a self-paced presentation time method to obtain behavioural indicators of verbal rehearsal. In addition, subsequent trial-by-trial self-reports were gathered. Word length effects in recall suggested that phonological recoding (converting images to names – a necessary precursor for rehearsal) took place, with evidence of more rehearsal among children with higher performance levels. According to self-paced presentation times, cumulative rehearsal was the dominant form of rehearsal only for children with higher spans on difficult trials. The combined results of self-paced times and word length effects in recall suggest that "naming" as simple form of rehearsal was dominant for most children. Self-reports were in line with these conclusions. Additionally, children used a mixture of strategies with considerable intra-individual variability, yet strategy use was nevertheless linked to age as well as performance levels.